Hubungan antara Indeks Massa Tubuh dengan Hernia Inguinalis di Poli Bedah RSUD Sanjiwani Gianyar - Ida Bagus Yoga Nugraha; S. N, Suriana; Ni Putu Diah Witari (Aesculapius Medical Journal, 2022)
ABSTRACT Inguinal hernia is a problem that is commonly found in surgical cases and can be suffered by all ages. Inguinal hernias are commonly found in men than women, risk factors that can be the etiology of inguinal hernias are increased intra-abdominal and abdominal wall muscle weakness. Overweight and obesity are risk factors that can influence or increase the occurrence of inguinal hernia. However, several studies have a different opinion, that the case of inguinal hernia is fewer in obesity and overweight compared to normal weight. The body mass index factor relation with inguinal hernia is the main focus on this study. This study aims to determine the relationship between Body Mass Index and Inguinal Hernia at the Surgical Clinic of the Sanjiwani Hospital. This study used an observational analytic research method with a cross sectional study design. The sampling technique used was purposive sampling method. The samples obtained were then analyzed and statistically tested with Chi-Square. The samples obtained were 135 patients, consisting of 64 (47.4%) diagnosed inguinal hernia and 71 (52.6%) undiagnosed inguinal hernia. To see the significance of the effect of BMI on the incidence of inguinal hernia, a Chi Square test was carried out with a significance value of 0.05. The p value of the chi square test carried out is 0.220. This value is more than 0.05 so it can be concluded that BMI has no impactful effect on the incidence of inguinal hernia.